2015
DOI: 10.1177/0956462415577496
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of contemporary models of shared HIV care and HIV in primary care in high-income settings

Abstract: HIV shared care is uncommon in the UK although shared care could be a beneficial model of care. We review the literature on HIV shared care to determine current practice and clinical, economic and patient satisfaction outcomes. We searched MEDLINE, EMBASE, NICE Evidence, Cochrane collaboration, Google and websites of the British HIV Association, Aidsmap, Public Health England, World Health Organization and Terrence Higgins Trust using relevant search terms in August 2014. Studies published after 2000, from hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 23 publications
2
31
0
Order By: Relevance
“…This finding is consistent with a small quantitative literature on HIV and primary care integration [64, 65] and found effective in high income settings [66, 67]. Several themes supported this finding (cessation support services for substance users, active referrals, and case management team counseling), highlighting the many ways in which integration could be effectively implemented [14, 17, 3336, 39, 40, 43, 4446, 48, 52].…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with a small quantitative literature on HIV and primary care integration [64, 65] and found effective in high income settings [66, 67]. Several themes supported this finding (cessation support services for substance users, active referrals, and case management team counseling), highlighting the many ways in which integration could be effectively implemented [14, 17, 3336, 39, 40, 43, 4446, 48, 52].…”
Section: Discussionsupporting
confidence: 93%
“…The need for greater involvement and the integration of primary care into the care of people living with HIV is well established,[ 15 17 , 41 ] but HIV shared care remains a fluid concept without a universally accepted definition. [ 32 ] Our findings support the need to advance our understanding of how shared care models can ensure comprehensive, timely, and accessible care for people living with HIV.…”
Section: Discussionsupporting
confidence: 55%
“…All settings were very team oriented, likely reflecting the needs of the evolving epidemic. [ 32 ] Team work has been identified to be important to an HIV care settings’ ability to provide comprehensive services for people living with HIV in both primary and specialist care settings. [ 33 ] Settings further performed well on critical HIV care measures, such as the ability to conduct HIV-related blood tests.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of shared care in HIV medicine found no consistent association with improved clinical outcomes, cost effectiveness, or acceptability, but the quality of studies was again judged to be poor [25]. A study of patients in care for HIV infection in Ontario, Canada found colorectal cancer screening was more common among patients receiving care from both generalists and specialists, compared with only HIV specialists [26].…”
Section: Discussionmentioning
confidence: 99%